2017
DOI: 10.3847/1538-4357/aa7898
|View full text |Cite
|
Sign up to set email alerts
|

Constraints to Dark Energy Using PADE Parameterizations

Abstract: We put constraints on dark energy (DE) properties using PADE parameterization, and compare it to the same constraints using Chevalier-Polarski-Linder (CPL) and ΛCDM, at both the background and the perturbation levels. The DE equation of the state parameter of the models is derived following the mathematical treatment of PADE expansion. Unlike CPL parameterization, PADE approximation provides different forms of the equation of state parameter that avoid the divergence in the far future. Initially we perform a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 152 publications
(243 reference statements)
6
57
0
Order By: Relevance
“…For all considered models we have also founded the redshift, for which the Universe starts to accelerate. The results vary from z tr = 0.9 (for the case 1) to z tr = 0.66 for the ΛCDM, all in good agreement with recent works [71][72][73]77].…”
Section: Discussionsupporting
confidence: 90%
“…For all considered models we have also founded the redshift, for which the Universe starts to accelerate. The results vary from z tr = 0.9 (for the case 1) to z tr = 0.66 for the ΛCDM, all in good agreement with recent works [71][72][73]77].…”
Section: Discussionsupporting
confidence: 90%
“…We found that the Hubble parameter in HDE cosmologies is ∼ 0.9 − 1.2% smaller than the ΛCDM model at low redshifts. We also showed that in HDE, cosmologies the universe changes its phase from decelerating to accelerating expansion at z tr ∼ 0.7 which in 1σ error is consistent with observations [see also 83,[113][114][115].…”
Section: Discussionsupporting
confidence: 89%
“…and the model of order (0, 2) gives H 0 = 68.8 ± 2.0 km/s/Mpc (68% C.L. ), both of which are in good accordance with the results from different analysis that employ the Padé parameterization (Rezaei et al 2017;Mehrabi & Basilakos 2018;Capozziello & Sen 2019).…”
Section: Resultssupporting
confidence: 88%